Handbook of foaming and blowing agents - Wypych, George (ChemTec Publishing, 2017)
"A variety of foaming techniques and equipment are available to produce very diverse range of products. Several monographic sources are available to learn about these methods of production but very little is known and discussed about the composition of materials to be processed and additives enhancing foamed products and making the foam production more economical. This book concentrates on the selection of additives for these diverse foaming processes which can be enhanced using available today, modern, chemical means to improve product quality, speed up the process, and broaden the range of products which can be produced using foaming technology. This book has also companion Databook of Blowing and Auxiliary Agents which contains data for these diverse chemical components of formulations of foamed materials and reveals their roles in foaming processes. There is no information which is repeated in both books. They do complement each other giving reader comprehensive information on the subject never published before with such a breadth."--